Description of a new species of Chlorotabanus (Insecta, Diptera, Tabanidae) from Neotropical Region - Krolow, Tiago Kütter; Henriques, Augusto Loureiro (Iheringia - Serie Zoologia, 2009)
We described a new species of Tabanidae (Diptera), Chlorotabanus flagellatus sp. nov., distributed in the Amazon region, in the States of Amazonas and Pará. Diagnosis, discussion and illustrations of external and internal characters are provided.
Descrição de uma nova espécie de chlorotabanus (insecta, diptera, tabanidae) da região neotropical
Keywords: Chlorotabanus; Diptera; Insecta; Tabanidae